Chicago Paper - Microstructure of Steel (See Discussion, "Physics of Steel," vol. xxiii.) - Albert Sauveur (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1894)
The following propositions and corollaries are intended to present, as concisely as possible, some of the evidences gathered while studying the microstructure of steel. Each proposition is accompanied by photo-micrographs showing the structure of illustrative samples. But it must be understood that the special instances thus chosen for illustration are by no means the only ones on the examination of which the propositions are based. On the contrary, they have been taken almost at random among a great many, in some instances more than a hundred, similar cases. Proposition I. A slow and undisturbed cooling from a temperature x or higher produces crystallization. Plate L, Plate II., Fig. 1, and Plate V., Figs. 1, 2, 3 and 4 show the crystalline structure of several pieces of steel. Plate I. reveals this structure in the center of a slowly-cooled Bessemer ingot, 1.5 feet from the top. Plate II., Pig. 1, is from a small 2-in, square testingot of the same heat, slowly cooled. Plate V., Figs. 1, 2, 3 and 4 show the structure of different parts of steel rails. The original photographs were all magnified 70 diameters, and have been reduced in engraving to 63, or to 55 diameters, as shown in the plates. Proposition 11. Undisturbed cooling from an initial temperature lower than x is not accompanied by crystallization. Plate III., Fig. 5, shows the structure of a piece of rail-steel forged from a white heat until it had fallen to dull-red. The structure is almost amorphous. Practically no crystallization has taken place during the subsequent cooling. Corollary.—Pieces of steel finished at a temperature lower than x do not take a crystalline structure.